Antioxidant metabolism in coffee (Coffea arabica L.) plants in response to nitrogen supply - Reis, André R. [UNESP]; Favarin, José L.; Gratão, Priscila L. [UNESP]; Capaldi, Flávia R.; Azevedo, Ricardo A. (Springer Nature, 2015)
Nitrogen (N) is the main element required for plant development. N fertilization interferes directly in N content in tissues, antioxidant systems, chlorophyll content and photosynthesis. We investigated the action of three levels of N (0, 150 and 300 kg N ha−1) in coffee (Coffea arabica L.) cv. Catuaí Vermelho IAC 44 leaves of plants during distinct fruit development stages (from pinhead drop to dried fruit). Leaf N content, net photosynthesis, chlorophyll content, total soluble protein and the activities of catalase, superoxide dismutase, guaiacol peroxidase and ascorbate peroxidase were analyzed. Leaf N content, net photosynthesis, chlorophyll and protein content increased significantly with N supply (N deficient plants exhibited visual symptoms of chlorosis). Antioxidant enzymes showed increased specific activities during fruit development, and decreases with N fertilization, being higher in absence of N. We identified two bands of Mn–SOD with increased activities and one of Fe–SOD, but they did not exhibit high SOD activity remaining essentially constant. Curiously, Cu/Zn–SOD isoenzymes were not detected, despite the fact that they are frequently abundant in plants. A relationship between N fertilization and antioxidant enzyme activities were founded in coffee leaves during fruit development indicating high activity of enzymatic antioxidant system during the coffee fruit ripening stage.
Keywords: Antioxidants; Coffea arabica; Nitrogen nutrition; Oxidative stress; Plant nutrition